Uncovering the secretome of mesenchymal stromal cells exposed to healthy, traumatic, and degenerative intervertebral discs: a proteomic analysis - Wangler, Sebastian (Stem Cell Res Ther, 2021)
BACKGROUND: Mesenchymal stromal cells (MSCs) have been introduced as promising cell source for regenerative medicine. Besides their multilineage differentiation capacity, MSCs release a wide spectrum of bioactive factors. This secretome holds immunomodulatory and regenerative capacities. In intervertebral disc (IVD) cells, application of MSC secretome has been shown to decrease the apoptosis rate, induce proliferation, and promote production of extracellular matrix (ECM). For clinical translation of secretome-based treatment, characterization of the secretome composition is needed to better understand the induced biological processes and identify potentially effective secretomes. METHODS: This study aimed to investigate the proteome released by bone marrow-derived MSCs following exposure to a healthy, traumatic, or degenerative human IVD environment by mass spectroscopy and quantitative immunoassay analyses. Exposure of MSCs to the proinflammatory stimulus interleukin 1β (IL-1β) was used as control. RESULTS: Compared to MSC baseline secretome, there were 224 significantly up- or downregulated proteins following healthy, 179 following traumatic, 223 following degenerative IVD, and 160 proteins following IL-1β stimulus. Stimulation of MSCs with IVD conditioned media induced a more complex MSC secretome, involving more biological processes, compared to stimulation with IL-1β. The MSC response to stimulation with IVD conditioned medium was dependent on their pathological status. CONCLUSIONS: The MSC secretome seemed to match the primary need of the IVD: homeostasis maintenance in the case of healthy IVDs, versus immunomodulation, adjustment of ECM synthesis and degradation disbalance, and ECM (re) organization in the case of traumatic and degenerative IVDs. These findings highlight the importance of cell preconditioning in the development of tailored secretome therapies. GRAPHICAL ABSTRACT: The secretome of human bone marrow-derived mesenchymal stromal cells (MSCs) stimulated with intervertebral disc (IVD) conditioned medium was analyzed by proteomic profiling. Depending on the pathological state of the IVD, the MSC secretome protein composition indicated immunomodulatory or anabolic activity of the secretome. These findings may have implications for tailored secretome therapy for the IVD and other tissues. [Image: see text]